Film and method for producing film

JP7635027B2Active Publication Date: 2025-02-25SUMITOMO CHEM CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021039756
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-11
Publication Date
2025-02-25
Estimated Expiration
2041-03-11

AI Technical Summary

Benefits of technology

【0008】 本発明によれば、膜残りの発生を抑制することができるフィルム、および、フィルムの製造方法を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007635027000001
    Figure 0007635027000001
Patent Text Reader

Abstract

To provide a film capable of suppressing an occurrence of a film residue and also to provide a manufacturing method of a film.SOLUTION: The film includes a phase separation structure layer containing at least two kinds of olefinic polymer and having a sea-island type phase separation structure composed of a continuous phase and a non-continuous phase. In the phase separation structure layer, a cross section in a TD direction satisfies the following equation (1): 1.26≤S1 / S2 (1) (In the equation, S1 denotes an average area of the non-continuous phase in an area from one surface to thickness 0% to 4% based on thickness of the phase separation structure layer 100%. S2 denotes an average area of the non-continuous phase in an area from one surface to thickness 48% to 52% based on the thickness of the phase separation structure layer 100%.).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a film and a method for making the film. [Background technology]

[0002] In recent years, the need for quick cooking and universal design has led to an increased demand for easy-peel packaging materials. Composite films in which a base film and an easy-peel film are laminated are widely used as easy-peel packaging materials. Easy-peel films are generally composed of multiple layers. For example, Patent Document 1 discloses a film composed of an outer layer containing a propylene-based polymer, an intermediate layer containing a propylene-based polymer and an ethylene homopolymer, and a seal layer. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2020-1386 A Summary of the Invention [Problem to be solved by the invention]

[0004] A composite film obtained by laminating a base film and an easy-peel film is used, for example, as a lid material for a cup container for jelly, pudding, etc. However, a lid material using a conventional composite film has a risk of generating a so-called film residue, that is, a part of the film remains on the container in a film-like form when the lid is peeled off.

[0005] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a film capable of suppressing the occurrence of film residue, and a method for producing the film. [Means for solving the problem]

[0006] The film of the present invention contains at least two kinds of olefin-based polymers and is provided with a phase-separated structure layer having an islands-in-a-sea type phase-separated structure consisting of a continuous phase and a discontinuous phase, and the phase-separated structure layer has a cross section in the TD direction that satisfies the following formula (1): 1.26≦S1 / S2 (1) (In the formula, S1 represents the average area of ​​the discontinuous phase in a region from one surface to 0% to 4% of the thickness relative to 100% of the thickness of the phase-separated structure layer. S2 represents the average area of ​​the discontinuous phase in a region from one surface to 48% to 52% of the thickness relative to 100% of the thickness of the phase-separated structure layer.)

[0007] The method for producing a film according to the present invention is a method for producing the above-mentioned film, and includes the steps of melt-kneading a composition containing at least two kinds of olefin polymers, extruding the melt-kneaded composition onto a cooling roll rotating at a speed of 50 m / min or more, and forming the extruded composition into a film. Effect of the Invention

[0008] According to the present invention, it is possible to provide a film capable of suppressing the occurrence of film residue, and a method for producing the film. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] Hereinafter, an embodiment of the present invention will be described, however, the present invention is not limited to the following embodiment.

[0010] [film] The film according to this embodiment includes a phase-separated structure layer that contains at least two kinds of olefin polymers and has an islands-in-the-sea type phase-separated structure composed of a continuous phase and a discontinuous phase.

[0011] Examples of the olefin polymer include propylene polymers and ethylene polymers.

[0012] The propylene-based polymer is a propylene homopolymer or a propylene-based copolymer containing 50% by mass or more of structural units derived from propylene. Examples of structural units other than propylene contained in the propylene-based copolymer include structural units derived from ethylene and α-olefins having 4 to 12 carbon atoms.

[0013] Examples of the propylene-based copolymer include propylene-based random copolymers, such as propylene-ethylene random copolymers, propylene-α-olefin random copolymers, and propylene-ethylene-α-olefin terpolymers.

[0014] Examples of the α-olefin include α-olefins having 4 to 12 carbon atoms, such as 1-butene, 2-methyl-1-propene, 1-pentene, 2-methyl-1-butene, 3-methyl-1-butene, 1-hexene, 2-ethyl-1-butene, 2,3-dimethyl-1-butene, 2-methyl-1-pentene, 3-methyl-1-pentene, 4-methyl-1-pentene, 3,3-dimethyl-1-butene, 1-heptene, and methyl-1-heptene. Examples of the copolymerizable copolymer include 1-butene, dimethyl-1-pentene, ethyl-1-pentene, trimethyl-1-butene, methylethyl-1-butene, 1-octene, methyl-1-pentene, ethyl-1-hexene, dimethyl-1-hexene, propyl-1-heptene, methylethyl-1-heptene, trimethyl-1-pentene, propyl-1-pentene, diethyl-1-butene, 1-nonene, 1-decene, 1-undecene, and 1-dodecene. Preferred are 1-butene, 1-pentene, 1-hexene, or 1-octene, and more preferably 1-butene or 1-hexene from the viewpoints of copolymerization characteristics, economic efficiency, and the like, and further preferably 1-butene.

[0015] The propylene-based polymer is preferably a propylene homopolymer or a propylene-based random copolymer, more preferably a propylene homopolymer or a propylene-ethylene random copolymer. The phase-separated structure layer may contain only one type of propylene-based polymer, or may contain two or more types of propylene-based polymers having different types or contents of structural units.

[0016] When the propylene-based polymer is a propylene-ethylene random copolymer, the content of structural units derived from ethylene is usually 0.1 to 20 mass%, preferably 0.5 to 10 mass%, more preferably 0.5 to 6 mass%, and even more preferably 2 to 6 mass%.

[0017] When the propylene-based polymer is a propylene-ethylene-α-olefin terpolymer, the content of the structural units derived from ethylene is usually 0.1 to 20 mass%, preferably 0.5 to 10 mass%, more preferably 0.5 to 5 mass%, and even more preferably 0.5 to 3 mass%. The content of the structural units derived from α-olefin is usually 0.1 to 20 mass%, preferably 0.5 to 10 mass%, more preferably 1 to 10 mass%, and even more preferably 3 to 10 mass%.

[0018] The melting point of the propylene polymer is preferably from 120°C to 170°C, and more preferably from 130°C to 170°C, from the viewpoint of heat resistance.

[0019] Examples of methods for producing propylene-based polymers include a method for homopolymerizing propylene in the presence of a Ziegler-Natta catalyst or a metallocene catalyst, and a method for copolymerizing propylene with an olefin other than propylene. The Ziegler-Natta catalyst is a catalyst that uses a combination of a titanium-containing solid transition metal component and an organometallic component. The metallocene catalyst is a catalyst that uses a combination of a transition metal compound of Groups 4 to 6 of the periodic table that has at least one cyclopentadienyl skeleton and a cocatalyst component. Examples of the polymerization method include slurry polymerization and solution polymerization carried out in an inert hydrocarbon solvent, and liquid phase polymerization and gas phase polymerization carried out in the absence of a solvent.

[0020] In the production of a propylene-based polymer, the propylene-based polymer may be dried at a temperature equal to or lower than the melting temperature of the produced propylene-based polymer in order to remove residual solvents, ultralow molecular weight oligomers produced as by-products during the production, etc. Examples of the drying method include the methods described in JP-A-55-75410 and JP-A-2565753.

[0021] The material containing at least two kinds of propylene-based polymers may be a multistage polymer obtained by producing in two or more stages and composed of at least two kinds of propylene-based polymer components. The combination of the propylene-based polymer components in the propylene-based multistage polymer may be a combination of propylene homopolymer components, a combination of a propylene homopolymer component and a propylene copolymer component, or a combination of propylene copolymer components. The propylene-based multistage polymer preferably contains a polymer component (A) containing 90% by mass or more of a propylene-derived structural unit, and a copolymer component (B) containing a propylene-derived structural unit and one or more structural units selected from the group consisting of ethylene and α-olefins having 4 to 12 carbon atoms. The polymer component (A) is preferably a propylene homopolymer component, and the copolymer component (B) is preferably a propylene copolymer component.

[0022] The content of structural units derived from propylene contained in the polymer component (A) contained in the propylene-based multistage polymer is 90 to 100 mass%, preferably 95 to 100 mass%. The content of ethylene contained in the copolymer component (B) is usually 10 to 50 mass%, preferably 15 to 50 mass%, more preferably 20 to 40 mass%. The content of the copolymer component (B) contained in the propylene-based multistage polymer is usually 7 to 70 mass%, preferably 10 to 50 mass%, more preferably 10 to 40 mass%.

[0023] When the phase-separated structure layer contains two or more kinds of propylene-based polymers, it is preferable that at least one kind of propylene-based polymer is a propylene homopolymer or a propylene random copolymer and at least one other kind of propylene-based polymer is a propylene multistage polymer, and it is more preferable that at least one kind of propylene-based polymer is a propylene homopolymer and at least one other kind of propylene-based polymer is a propylene multistage polymer.

[0024] The ethylene-based polymer is an ethylene homopolymer or an ethylene copolymer containing 50% by mass or more of structural units derived from ethylene. The ethylene-based polymer is preferably an ethylene homopolymer.

[0025] The density of the ethylene homopolymer is preferably 930 kg / m 3 More preferably, it is 910 to 925 kg / m 3 and more preferably 915 to 925 kg / m 3 It is.

[0026] The ethylene homopolymer is preferably produced by a so-called "high pressure process." The production of the ethylene homopolymer by the "high pressure process" is generally carried out by polymerizing ethylene in the presence of a radical generator at a polymerization pressure of 140 to 300 MPa and a polymerization temperature of 200 to 300°C using a tank reactor or a tubular reactor.

[0027] The method for producing the ethylene copolymer includes a known polymerization method using a known radical polymerization catalyst or ionic polymerization catalyst. Examples of known catalysts include peroxide catalysts, Ziegler-Natta catalysts, metallocene catalysts, etc. Examples of known polymerization methods include solution polymerization, slurry polymerization, high pressure ionic polymerization, high pressure radical polymerization, gas phase polymerization, etc.

[0028] From the viewpoint of controlling the ratio (S1 / S2) of S1 and S2 described later, the phase-separated structure layer preferably contains a propylene-based polymer and an ethylene-based polymer as the at least two kinds of olefin-based polymers.More preferably, the phase-separated structure layer contains a propylene homopolymer, a propylene random copolymer, and an ethylene-based polymer as the at least two kinds of olefin-based polymers.More preferably, the phase-separated structure layer contains a propylene multistage polymer, a propylene random copolymer, and an ethylene-based polymer as the at least two kinds of olefin-based polymers.

[0029] The content of the propylene-based polymer contained in the phase-separated structure layer is 65 to 95 mass%, preferably 75 to 95 mass%, more preferably 75 to 90 mass%, and even more preferably 80 to 90 mass%, based on 100 mass% of the total amount of the propylene-based polymer and the ethylene-based polymer in the phase-separated structure layer. The content of the ethylene-based polymer contained in the phase-separated structure layer is 5 to 35 mass%, preferably 5 to 25 mass%, more preferably 10 to 25 mass%, and even more preferably 10 to 20 mass%, based on 100 mass% of the total amount of the phase-separated structure layer.

[0030] When the phase-separated structure layer is a layer containing two or more kinds of propylene-based polymers, at least one kind of propylene-based polymer is a propylene homopolymer or a propylene-based random copolymer, and at least another kind of propylene-based polymer is a propylene-based multistage polymer, the content of the ethylene-based polymer contained in the phase-separated structure layer is 5 to 35 mass%, preferably 10 to 30 mass%, more preferably 15 to 30 mass%, and even more preferably 20 to 30 mass%, based on 100 mass% of the total amount of the phase-separated structure layer. The total amount of the two or more propylene-based polymers contained in the phase-separated structure layer is 65 to 95 mass%, preferably 70 to 90 mass%, more preferably 70 to 85 mass%, and even more preferably 70 to 80 mass%, with the total amount in the phase-separated structure layer being 100 mass%. The content of the propylene-based multistage polymer contained in the phase-separated structure layer is preferably 5 to 40 mass%, more preferably 5 to 30 mass%, and even more preferably 10 to 30 mass%, with the total amount in the phase-separated structure layer being 100 mass%.

[0031] The phase separation structure layer is a layer made of a composition having a melt flow rate of preferably 1 to 30 g / 10 min, more preferably 2 to 30 g / 10 min, and even more preferably 2 to 25 g / 10 min, measured at a temperature of 230° C. and a load of 2.16 kg. Examples of methods for adjusting the melt flow rate include a method for adjusting the melt flow rate of a propylene-based polymer or an ethylene-based polymer contained in the composition, and a method for adjusting the composition by melt-kneading a propylene-based polymer and an ethylene-based polymer in the presence of an organic peroxide. Examples of organic peroxides include 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, 1,3-bis(tert-butylperoxyisopropyl)benzene, and 3,6,9-triethyl-3,6,9-trimethyl-1,4,7-triperoxonane.

[0032] When the phase separation structure layer contains a propylene-based polymer and an ethylene-based polymer, the film may be formed using pellets prepared by melt-kneading the propylene-based polymer and the ethylene-based polymer before film formation, or a mixture prepared by pellet blending in which the pellets are mixed without melting them may be formed. The propylene-based polymer may be one type only, or two or more types. When melt-kneading is performed, examples of the melt-kneading method include a method of heating and melting the propylene-based polymer and the ethylene-based polymer and kneading them using a multi-screw extruder such as a single-screw extruder or a twin-screw extruder, a roll kneader, a kneader, a Brabender plastograph, or a Banbury mixer, and among these, it is preferable to use a multi-screw extruder such as a single-screw extruder or a twin-screw extruder.

[0033] The temperature during the melt-kneading is preferably 180°C or higher and 350°C or lower, and more preferably 180°C or higher and 320°C or lower.

[0034] The composition constituting the phase separation structure layer may contain additives, other resins, etc., as necessary, within the scope of not impairing the object and effect of the present invention. Examples of additives include antioxidants, neutralizing agents, ultraviolet absorbers, antistatic agents, lubricants, nucleating agents, adhesives, antifogging agents, antiblocking agents, melt flow rate regulators, etc. Examples of other resins include styrene-butadiene-styrene copolymers, styrene-isoprene-styrene copolymers, and hydrogenated products of these copolymers.

[0035] The antioxidant is a compound that has the effect of preventing decomposition of polyolefin resins due to heat, light, oxygen, etc. Examples of the antioxidant include phenol-based antioxidants, phosphorus-based antioxidants, sulfur-based antioxidants, hydroxylamine-based antioxidants, and metal deactivators, and preferably the phenol-based antioxidants, phosphorus-based antioxidants, or sulfur-based antioxidants.

[0036] Examples of phenol-based antioxidants include 2,6-di-tert-butyl-4-methylphenol, tetrakis[methylene-3(3',5'-di-tert-butyl-4-hydroxyphenyl)propionate]methane, octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 3,9-bis[2-{3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionyloxy}-1,1-dimethylethyl]-2,4,8,10-tetraoxaspiro[5·5]undecane, 1, 3,5-Tris2[3(3,5-di-tert-butyl-4-hydroxyphenyl)propionyloxy]ethyl isocyanate, 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, tris(3,5-di-tert-butyl-4-hydroxybenzyl)isocyanurate, 1,3,5-tris(4-tert-butyl-3-hydroxy-2,6-dimethylbenzyl)isocyanurate, pentaerythrityl-tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyloxy]ethyl isocyanate 2,2'-methylene-bis-(4-methyl-6-tert-butylphenol), 2,2'-methylene-bis-(4-ethyl ... tert-butylphenol), 2,2'-methylene-bis-(4,6-di-tert-butylphenol), 2,2'-ethylidene-bis-(4,6-di-tert-butylphenol), 2,2'-butylidene-bis-(4-methyl-6-tert-butylphenol), 4,4'-butylidenebis(3-methyl-6-tert-butylphenol), 2-tert-butyl-6-(3-tert-butyl-2-hydroxy-5-methylbenzyl)-4-methylphenyl acrylate, 2,4-di-tert-amyl-6-(1-(3,5-di-tert-amyl-2-hydroxyphenyl)ethyl)phenyl acrylate, tocopherols. Examples of tocopherols include vitamin E, which is α-tocopherol, and preferably 2,6-di-tert-butyl-4-methylphenol, tetrakis[methylene-3(3',5'-di-tert-butyl-4-hydroxyphenyl)propionate]methane, 2,6-di-tert-butyl-4-methylphenol, octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 3,9-bis[2-{3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate]methane, [ethylphenyl)propionyloxy}-1,1-dimethylethyl]-2,4,8,10-tetraoxaspiro[5·5]undecane, tris(3,5-di-tert-butyl-4-hydroxybenzyl)isocyanurate or vitamin E, and more preferably tetrakis[methylene-3(3',5'-di-tert-butyl-4-hydroxyphenyl)propionate]methane, octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate or vitamin E.

[0037] The blending amount of the phenol-based antioxidant is generally 0.01 to 2 parts by mass, preferably 0.01 to 1 part by mass, and more preferably 0.01 to 0.5 parts by mass, relative to 100 parts by mass of the total mass of the phase-separated structure layer.

[0038] Examples of phosphorus-based antioxidants include tris(nonylphenyl)phosphite, tris(2,4-di-tert-butylphenyl)phosphite, distearyl pentaerythritol diphosphite, bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite, bis(2,4-di-tert-butyl-6-methylphenyl)pentaerythritol diphosphite, bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphite, bis(2,4-dicumylphenyl)pentaerythritol diphosphite, tetrakis(2,4-di-tert-butylphenyl)-4,4'-diphenylenediphosphonite, 2,2'-methylenebis(4,6-di-tert-butylphenyl)2-ethylhexylphosphite, 2,2'-ethylidenebis(4,6-di-tert-butylphenyl)fluorophosphite, Bis(2,4-di-tert-butyl-6-methylphenyl)ethyl phosphite, 2-(2,4,6-tri-tert-butylphenyl)-5-ethyl-5-butyl-1,3,2-oxaphosphorinane, 2,2',2''-nitrilo[triethyl-tris(3,3',5,5'-tetra-tert-butyl-1,1'-biphenyl-2,2'-diyl)phosphite, 2,4,8,10-tetra-tert-butyl-6-[3-(3- and 2,4,8,10-tetra-tert-butyl-6-[3-(3-methyl-4-hydroxy-5-tert-butylphenyl)propoxy]dibenzo[d,f][1,3,2]dioxaphosphepine, preferably tris(2,4-di-tert-butylphenyl)phosphite or 2,4,8,10-tetra-tert-butyl-6-[3-(3-methyl-4-hydroxy-5-tert-butylphenyl)propoxy]dibenzo[d,f][1,3,2]dioxaphosphepine.

[0039] The amount of the phosphorus-based antioxidant blended is generally 0.01 to 2 parts by mass, preferably 0.01 to 1 part by mass, and more preferably 0.01 to 0.5 parts by mass, relative to 100 parts by mass of the total mass of the phase-separated structure layer.

[0040] Examples of the sulfur-based antioxidant include dilauryl 3,3'-thiodipropionate, tridecyl 3,3'-thiodipropionate, dimyristyl 3,3'-thiodipropionate, distearyl 3,3'-thiodipropionate, laurylstearyl 3,3'-thiodipropionate, neopentanetetrayltetrakis(3-laurylthiopropionate), and bis[2-methyl-4-(3-n-alkyl(C12-C14)thiopropionyloxy)-5-tert-butylphenyl]sulfide, and preferably dilauryl 3,3'-thiodipropionate, dimyristyl 3,3'-thiodipropionate, or distearyl 3,3'-thiodipropionate.

[0041] The blending amount of the sulfur-based antioxidant is generally 0.01 to 2 parts by mass, preferably 0.01 to 1 part by mass, and more preferably 0.01 to 0.5 parts by mass, relative to 100 parts by mass of the total mass of the phase-separated structure layer.

[0042] Examples of the neutralizing agent include calcium stearate, hydrotalcite, alkaline earth metal oxides, and alkaline earth metal hydroxides. These neutralizing agents may be used alone or in combination of two or more.

[0043] Examples of other additives include lubricants such as higher fatty acid amides and higher fatty acid esters; antistatic agents such as glycerin esters of fatty acids having 8 to 22 carbon atoms, sorbitan acid esters, and polyethylene glycol esters; anti-blocking agents such as synthetic silica powder, synthetic aluminosilicate powder, polymer beads, and silicone resin compounds; and anti-fogging agents such as glycerin fatty acid esters, polyglycerin fatty acid esters, polyethylene glycol fatty acid esters, polyethylene glycol sorbitan fatty acid esters, polyoxyethylene alkyl ethers, sorbitan fatty acid esters, alkyldiethanolamines, and alkyldiethanolamides.

[0044] The phase-separated structure layer has an islands-in-a-sea type phase-separated structure consisting of a continuous phase and a discontinuous phase, and the cross section of the phase-separated structure layer in the TD direction satisfies the following formula (1). 1.26≦S1 / S2 (1) In formula (1), S1 indicates the average area of ​​the discontinuous phase in a region from one surface to 0% to 4% of the thickness of the phase-separated structure layer, relative to 100% of the thickness. S2 indicates the average area of ​​the discontinuous phase in a region from one surface to 48% to 52% of the thickness of the phase-separated structure layer, relative to 100% of the thickness. The average area of ​​the discontinuous phase is calculated by analyzing an image taken by a transmission electron microscope. Specifically, it can be determined by the method described in the Examples below.

[0045] It is preferable that the cross section of the phase-separated structure layer in the TD direction satisfies the following formula (2). 1.26≦S1 / S2≦1.50 (2) In formula (2), S1 and S2 have the same meaning as S1 and S2 defined above.

[0046] Here, the film formation direction (winding direction) is defined as the MD direction, the film thickness direction as the ND direction, and the direction perpendicular to the MD and ND directions as the TD direction. The cross section in the TD direction refers to a cross section whose direction coincides with the plane determined by the axes of the TD and ND directions.

[0047] The ratio of S1 to S2 (S1 / S2) is determined by setting the rotation speed of the cooling roll to 50 m / min or more, using at least two types of olefin polymers, and setting the resin pressure during extrusion to 50 kg / cm. 2 By doing so, it is possible to control the amount of the heat generated.

[0048] The continuous phase is the sea portion of an islands-in-a-sea type phase separation structure. The discontinuous phase is the island portion of an islands-in-a-sea type phase separation structure. From the viewpoint of controlling the ratio of S1 to S2 (S1 / S2), the continuous phase is preferably formed from a propylene-based polymer containing 90% by mass or more of structural units derived from propylene. From the viewpoint of controlling the ratio of S1 to S2 (S1 / S2), the discontinuous phase is preferably formed from at least one selected from the group consisting of propylene-based polymers and ethylene-based polymers containing less than 90% by mass of structural units derived from propylene.

[0049] The film according to the present embodiment may further comprise a sealing layer and / or an outer layer, and preferably the film according to the present embodiment further comprises a sealing layer.

[0050] The seal layer may contain, for example, a propylene-based random copolymer. The propylene-based random copolymer contained in the seal layer is preferably a propylene-ethylene random copolymer, a propylene-α-olefin random copolymer, or a propylene-ethylene-α-olefin terpolymer, more preferably a propylene-ethylene random copolymer or a propylene-ethylene-α-olefin terpolymer, and even more preferably a propylene-ethylene random copolymer. The seal layer may contain only one type of propylene-based random copolymer, or may contain two or more types.

[0051] When the propylene-based random copolymer contained in the seal layer is a propylene-ethylene random copolymer, the content of structural units derived from ethylene is usually 2 to 20 mass%, preferably 2 to 10 mass%, and more preferably 2 to 6 mass%. When the propylene-based random copolymer contained in the seal layer is a propylene-ethylene-α-olefin terpolymer, the content of the structural units derived from ethylene is usually 1 to 20 mass%, preferably 1 to 10 mass%, more preferably 1 to 5 mass%, and even more preferably 1 to 3 mass%. The content of the structural units derived from α-olefin is usually 1 to 20 mass%, preferably 1 to 10 mass%, more preferably 1 to 10 mass%, and even more preferably 1 to 5 mass%.

[0052] The melting point of the propylene-based random copolymer contained in the sealing layer is 150° C. or lower, and preferably 145° C. or lower.

[0053] The content of the propylene-based random copolymer having a melting point of 150° C. or less is preferably 80% by mass or more, more preferably 90% by mass or more, based on 100% by mass of the total mass of all components contained in the seal layer. The seal layer may contain an ethylene homopolymer or an ethylene-α-olefin copolymer (the ethylene-α-olefin copolymer contains 50% by mass or more of structural units derived from ethylene), and is preferably 20% by mass or less, more preferably 10% by mass or less, based on 100% by mass of the total mass of all components contained in the seal layer.

[0054] The outer layer may contain, for example, a propylene-based polymer. The propylene-based polymer contained in the outer layer is preferably a propylene homopolymer or a propylene random copolymer, more preferably a propylene homopolymer or a propylene-ethylene random copolymer. The outer layer may contain only one type of propylene-based polymer, or may contain two or more types of propylene-based polymers. The content of the propylene-based polymer is preferably 90% by mass or more, where the total mass of all components contained in the outer layer is 100% by mass. It is preferable that 95% by mass or more of the polymer components contained in the outer layer is a propylene-based polymer.

[0055] When the propylene-based polymer contained in the outer layer is a propylene-ethylene random copolymer, the content of structural units derived from ethylene is usually 0.1 to 20 mass%, preferably 0.1 to 10 mass%, more preferably 0.1 to 6 mass%, and even more preferably 0.1 to 5 mass%. When the propylene-based polymer contained in the outer layer is a propylene-ethylene-α-olefin terpolymer, the content of structural units derived from ethylene is usually 0.1 to 20 mass%, preferably 0.1 to 10 mass%, more preferably 0.1 to 5 mass%, and even more preferably 0.1 to 3 mass%. The content of structural units derived from α-olefin is usually 0.1 to 20 mass%, preferably 0.1 to 10 mass%, and more preferably 0.1 to 5 mass%.

[0056] The melting point of the propylene polymer contained in the outer layer is preferably 150° C. or higher, and more preferably 155° C. or higher.

[0057] The sealing layer and the outer layer may each contain the above-mentioned additives, other resins, etc., as necessary, within the scope of not impairing the object and effect of the present invention.

[0058] When the film of the present embodiment includes an outer layer, a phase-separation structure layer, and a seal layer, it is preferable that the phase-separation structure layer is disposed between the outer layer and the seal layer, and the seal layer is one of the surface layers of the film. It is preferable that the outer layer and the phase-separation structure layer are adjacent to each other, and that the phase-separation structure layer and the seal layer are adjacent to each other.

[0059] When the film of the present embodiment includes an outer layer, a phase-separation structure layer, and a seal layer, the thickness of the seal layer in the film is preferably 5% to 20% and more preferably 5% to 15% of the total thickness of the outer layer, the phase-separation structure layer, and the seal layer taken as 100%. The thickness of the outer layer is preferably 5% to 20% and more preferably 5% to 15% of the total thickness of the outer layer, the phase-separation structure layer, and the seal layer taken as 100%. The thickness of the phase-separation structure layer is preferably 60% to 90% and more preferably 70% to 90% of the total thickness of the outer layer, the phase-separation structure layer, and the seal layer taken as 100%.

[0060] When the film of the present embodiment includes an outer layer, a phase-separated structure layer, and a seal layer, the thickness of the film is preferably 5 μm to 500 μm, more preferably 20 μm to 100 μm, and even more preferably 20 μm to 50 μm. The total thickness of the outer layer, the phase-separated structure layer, and the seal layer is preferably 5 μm to 500 μm, more preferably 20 μm to 100 μm, and even more preferably 20 μm to 50 μm.

[0061] [Film manufacturing method] The film manufacturing method according to the present embodiment includes a step of melt-kneading a composition containing at least two types of olefin polymers (hereinafter, sometimes referred to as the "melt-kneading step"), a step of extruding the melt-kneaded composition onto a cooling roll rotating at a speed of 50 m / min or more (hereinafter, sometimes referred to as the "extrusion step"), and a step of forming the extruded composition into a film (hereinafter, sometimes referred to as the "film formation step").

[0062] In the melt-kneading step, a composition containing at least two kinds of olefin-based polymers is melt-kneaded. The melt-kneading method can be carried out using a conventionally known method and device. For example, the above-mentioned materials are mixed using a mixing device such as a Henschel mixer, a ribbon blender, or a tumbler mixer, and then melt-kneaded. The melt-kneading can be carried out using a device such as a single-screw extruder, a twin-screw extruder, a Banbury mixer, or a heat roll.

[0063] In the extrusion step, the composition melt-kneaded in the melt-kneading step is extruded onto a cooling roll rotating at a speed of 50 m / min or more. Methods for extruding the composition include conventionally known methods. For example, the T-die method and the tubular method are included, and the T-die method is preferred. The rotation speed of the cooling roll is 50 m / min or more, preferably 60 m / min or more, from the viewpoint of controlling the ratio of S1 to S2 (S1 / S2). The temperature of the cooling roll is preferably 20 to 80°C, more preferably 30 to 60°C. The resin pressure in the extrusion step is preferably 50 kg / cm. 2 More preferably, 100 kg / cm 2 That's all.

[0064] In the film-forming step, the composition extruded in the extrusion step is formed into a film. Specifically, the molten film formed in the extrusion step is cooled and solidified by a cooling roll rotating at high speed.

[0065] The film of the present embodiment may be formed into a multilayer film together with other compositions. When the film of the present embodiment includes an outer layer, a phase separation structure layer, and a seal layer, the film manufacturing method may be, for example, a T-die method, a tubular method, etc., and preferably a T-die method. Examples of the method for laminating each layer include a method in which molten resins flowing from multiple extruders are combined in layers in a die, and a method in which molten resins flowing from multiple extruders are sent to separate manifolds and combined in layers just before the lip of the die. In addition, the film of the present embodiment may be subjected to surface treatment such as corona discharge treatment, flame treatment, plasma treatment, and ozone treatment.

[0066] The film of the present embodiment can be used, for example, for packaging. Specifically, the film can be used for packaging food, textiles, miscellaneous goods, etc., and is preferably used for packaging retort food. For packaging retort food, the film can be used, for example, for packaging bags for retort food and packaging containers for retort food. The film of the present embodiment also has excellent heat resistance.

[0067] The film of the present embodiment may be a composite film in which a gas barrier layer or a substrate layer is laminated on the outer layer side of the film. Examples of the gas barrier layer include layers containing an ethylene-vinyl alcohol copolymer, an organic silicon compound, an inorganic layered compound, a metal, a metal oxide, etc. Examples of the substrate layer include a biaxially oriented polyester resin layer, a biaxially oriented polyamide resin layer, a biaxial polyolefin resin layer, etc. The substrate layer may be a multilayer of two or more of these resin layers.

[0068] Examples of a method for laminating the film of this embodiment with a gas barrier layer or a base layer include a dry lamination method and an extrusion lamination method.

[0069] The film and the method for producing the film according to the present embodiment are not limited to the above embodiment, and various modifications are possible without departing from the gist of the present invention. In addition, the configurations, methods, etc. of the embodiments other than the above may be arbitrarily adopted and combined, and the configurations, methods, etc. of one of the above embodiments may be applied to the configurations, methods, etc. of the other embodiments. EXAMPLES

[0070] The present invention will be described in more detail below with reference to examples, although the present invention is not limited to these examples.

[0071] The measured values ​​of each item in the examples and comparative examples were measured by the following methods.

[0072] <Contents (unit: mass%) of propylene-based polymer component (A) and propylene-based copolymer component (B) in propylene-based multistage polymer produced by multistage polymerization> The content (Pa) of the propylene-based polymer component (A) and the content (Pb) of the propylene-based copolymer component (B) in the propylene-based multistage polymer were determined from the mass balance during polymerization of the propylene-based polymer component (A) and the propylene-based copolymer component (B).

[0073] <Content of ethylene structural units in propylene copolymer component (B) in propylene multistage polymer produced by multistage polymerization (unit: mass%)> First, when the propylene-based polymer component (A) constituting the propylene-based multistage polymer was obtained, the IR spectrum of the propylene-based polymer component (A) was measured to determine the content (unit: mass%) of structural units derived from ethylene in the propylene-based polymer component (A). Next, the propylene-based multistage polymer was subjected to IR spectrum measurement, and the content (unit: mass%) of constitutional units derived from ethylene in the propylene-based multistage polymer was determined according to "(ii) Method for block copolymers" described on page 616 of Polymer Analysis Handbook (published by Kinokuniya Shoten in 1995). Then, the content (unit: mass %) of structural units derived from ethylene in the propylene-based copolymer component (B) was calculated by the following formula (3). EB = (ET x 100 - EA x Pa) / Pb (3) (In the formula, EB represents the content of structural units derived from ethylene in the propylene-based copolymer component (B). ET represents the content of structural units derived from ethylene in the propylene-based multistage polymer. Pa represents the content of propylene-based polymer component (A) in the propylene-based multistage polymer. Pb represents the content of propylene-based copolymer component (B) in the propylene-based multistage polymer. EA represents the content of structural units derived from ethylene in the propylene-based polymer component (A).)

[0074] <Melt flow rate (MFR, unit: g / 10 min)> The melt flow rate of the propylene-based polymer was measured at a temperature of 230° C. and a load of 2.16 kg in accordance with Method A specified in JIS K7210-1. The melt flow rate of the ethylene polymer was measured at a temperature of 190° C. and a load of 2.16 kg in accordance with Method A specified in JIS K7210-1.

[0075] <Density (unit: kg / m 3 )> The density of the ethylene polymer was measured according to the method specified in JIS K7112-1980, Method A. The sample was subjected to annealing as described in JIS K6760-1995.

[0076] <Melting point (unit: °C)> Using a differential scanning calorimeter (PerkinElmer), an aluminum pan containing about 10 mg of sample was (i) held at 240°C for 5 minutes under a nitrogen gas atmosphere, then (ii) cooled from 240°C to 40°C at a rate of 10°C / min. Next, (iii) held at 40°C for 5 minutes, then (iv) heated from 40°C to 240°C at a rate of 10°C / min. The temperature of the maximum peak of the melting endothermic curve obtained by the calorimetry in the process (iv) was taken as the melting point (Tm). The melting point of indium (In) measured in the same manner as above, except that the temperature was raised at a rate of 5°C / min in the process (iv), was 156.6°C.

[0077] <Transmission electron microscope> The film or composite film was embedded in resin, then stained with an aqueous solution of ruthenium tetroxide, and a cross section determined by the TD and ND directions of the film was cut out with a cryomicrotome to prepare an ultrathin sample with a thickness of 200 nm or less. The ultrathin sample was placed on a mesh for observation, and then photographed with a transmission electron microscope (Hitachi High-Tech, H-7650) at an accelerating voltage of 100 kV and an observation magnification of 20,000 times to take Image 1, which includes the area to be selected in step 2) of the image analysis described below, and Image 2, which includes the area to be selected in step 16).

[0078] <Image analysis> The captured images were analyzed to calculate the average areas S1 and S2 of the discontinuous phase. The analysis was performed using image analysis software "NS2K-Pro" (manufactured by Nano Systems Co., Ltd.). The captured images were analyzed according to the following procedure.

[0079] 1) Open Image 1, select "Scale", and execute "Set Scale (from Image)" to set the scale appropriately. 2) Select "Area Setting" and execute "Rectangular" to select a rectangular area that is 4 μm long in the TD direction and is located in an area of ​​48 to 52% of the thickness of the layer (second layer (phase-separated structure layer)) that forms the sea-island type phase separation structure, assuming the thickness of the layer to be 100%. 3) Select "Color Extraction" and perform "Monochrome Conversion". 4) Select "Binarization" and run "Discriminant Analysis (9 divisions)". 5) Select "Binary Processing" and perform "Black and White Inversion". 6) Select "Binary Processing", select "Select Image by Feature", select "Area", execute "8 Neighborhood", and select 0.001μm 2 The following noise images are removed: 7) Select "Binary Processing", execute "Remove Image from Processing Area", and select all four sides of the rectangle. 8) Select "Measure" and run "Area Measurement" to calculate the area of ​​each image identified as a non-continuous phase and obtain a list. 9) From the list of areas for each image obtained, find the first quartile and call it X. 10) Calculate Y from the following formula. Y=12000×X-5 (However, Y will be rounded off to the nearest 100, and any number less than 5 will be rounded down to 5.) 11) Using the image converted to monochrome in step 3), perform "shading processing" and "density unevenness correction" under the following conditions. Density of measurement target: Darker than background Approximate size of object: Y 12) Select "Binarization" and run the "NS method" under the following conditions. Density of the measurement target image: Darker than the background Sharpness: 70 Sensitivity: 6 Noise Reduction:Selected Concentration range used for extraction: 0 to 255 13) Select "Binary Processing", select "Select Image by Feature", select "Area", execute "8 Neighborhood", and select 0.001μm 2 The following noise images are removed: 14) Select "Binary Processing", execute "Image Removal on Processing Area", and select all four sides of the rectangle. 15) Select “Measure” and run “Area Measurement” to calculate the area of ​​each image identified as a discontinuous phase, and the calculated average was designated as S2. 16) Open Image 2, select "Area Setting", and execute "Rectangular" to select a rectangular area that is 4 μm long in the TD direction and is located in an area of ​​0 to 4% in the thickness direction from one surface of the layer (the boundary between the first layer (seal layer) if it is adjacent) when the thickness of the layer (second layer (phase separation structure layer)) that forms the sea-island type phase separation structure is taken as 100%. 17) Select "Color Extraction" and perform "Monochrome Conversion". 18) Step 11) was performed using the image converted to monochrome in step 17), and then the same operations as steps 12) to 15) were performed to calculate the area, and the average was designated as S1.

[0080] <Peel test> The composite film and the polypropylene sheet were overlapped so that the first layer of the composite film obtained in each Example was in contact with the 100 μm-thick polypropylene sheet, and heat-sealed under the following conditions using a heat sealer (manufactured by Toyo Tester Kogyo Co., Ltd.) to obtain a sample. Samples were obtained by heat-sealing so that the upper seal bar was in contact with the biaxially oriented nylon film of the composite film and the lower seal bar was in contact with the polypropylene sheet. Seal bar: Flat double-sided heating Sealing temperature: Upper seal bar: 180℃, Lower seal bar: 80℃ Sealing pressure: 2.0kg / cm 2 Sealing time: 1.0sec Seal width: 10mm For the obtained samples, the long side was parallel to the seal width direction, and the short side was perpendicular to the seal width direction, and test pieces with a short side length of 15 mm were cut out. The test pieces included a seal part of 10 mm x 15 mm. Five test pieces were prepared for each sample. Next, the seal part of the obtained test pieces was peeled in the long side direction from the start of peeling to a peel length of 25 mm at a tensile speed of 200 mm / min using a tensile tester (Tensilon manufactured by Orientec Co., Ltd.) while keeping the composite film and sheet bent at 90°, and a peel strength curve of peel length-peel load was obtained. A peel test was performed on five test pieces for each sample, and the sealing strength and peel strength were obtained by the sealing strength and peel strength test method described later. The sealing strength and peel strength were the average values ​​of the test results of five samples for each sample. In addition, the film residue was evaluated by the film residue test method described later.

[0081] <Sealing strength (N / 15mm)> If the peel load shows a maximum value within the peel length range of 0 mm to 5 mm, and the maximum value is 8 N / 15 mm or more, the seal strength is excellent. If it is 15 N / 15 mm or less, a person can open it without difficulty. The maximum value of the peel load within the peel length range of 0 mm to 5 mm was defined as the seal strength per 15 mm width.

[0082] <Peel strength (N / 15mm)> If the peel load shows a maximum value within the peel length range of 0mm to 5mm, the test piece can be peeled off without breaking up to a peel length of 25mm, the average peel load within the peel length range of 10mm to 20mm is 5 to 16N / 15mm, and the difference between the maximum and minimum peel loads within the peel length range of 10mm to 20mm is 5N / 15mm or less, then the peeling will be felt to be appropriately easy when peeled off by a person. The average peel load within the peel length range of 10mm to 20mm was taken as the peel strength per 15mm width.

[0083] <Film Remaining> In the above-mentioned peel test, peeling was started from one end of the sealed part of the test piece, and if the composite film and sheet separated when the peeling reached the other end, it was judged that there was no "film residue". On the other hand, if the composite film and sheet did not separate even after the peel length reached 25 mm, it was judged that there was "film residue". Each sample was tested five times, and if there was one or less sample with "film residue", it was judged as "no film residue and good peeling behavior (○)", if there were two or three samples with "film residue", it was judged as "some film residue (△)", and if there were four or more samples with "film residue (X)".

[0084] The components used in the examples and comparative examples are as follows.

[0085] Ingredients of [First layer (sealing layer)]

[0086] [PP1] Propylene and ethylene were copolymerized in the gas phase in the presence of a Ziegler-Natta catalyst to obtain a powder of a propylene-ethylene random copolymer having a melting point of 142°C and a melt flow rate of 6.0 g / 10 min measured at 230°C. The obtained propylene-ethylene random copolymer is hereinafter referred to as PP1.

[0087] Ingredients of the second layer (phase-separated structure layer)

[0088] [PP2] Propylene was polymerized in the gas phase in the presence of a Ziegler-Natta catalyst to obtain a propylene homopolymer powder having a melting point of 161°C and a melt flow rate of 2.0 g / 10 min measured at 230°C. The obtained propylene homopolymer is hereinafter referred to as PP2.

[0089] [PP3] In the first step, propylene was polymerized in the gas phase in the presence of a Ziegler-Natta catalyst, and then in the second step, propylene and ethylene were copolymerized in the gas phase to obtain a propylene-based multistage polymer consisting of a propylene homopolymer component (A) and a propylene-ethylene random copolymer component (B). The obtained propylene-based multistage polymer is hereinafter referred to as PP3. In PP3, the content of the propylene homopolymer component (A) was 77% by mass, the content of the propylene-ethylene random copolymer component (B) was 23% by mass, and the content of structural units derived from ethylene in the propylene-ethylene random copolymer component (B) was 30% by mass.

[0090] [PP4] 0.05% by weight of calcium stearate, 0.005% by weight of hydrotalcite, 0.15% by weight of Irganox 1010, and 0.1% by weight of Irgafos 168 (BASF, antioxidant) were added to 100 parts by weight of PP2, and the mixture was melt-kneaded in a twin-screw extruder to obtain pellets. The obtained pellets are hereinafter referred to as PP4.

[0091] [PP5] 0.005% by mass of calcium hydroxide, 0.075% by mass of Sumilizer GP, and 0.03% by mass of Sumilizer GS (Sumitomo Chemical Co., Ltd., antioxidants) were added to 100 parts by weight of PP3, and the mixture was melt-kneaded in a twin-screw extruder to obtain pellets. The obtained pellets are hereinafter referred to as PP5.

[0092] [PE1] Sumikathene G201-F (manufactured by Sumitomo Chemical Co., Ltd.), an ethylene homopolymer, was used. The melt flow rate measured at 190°C was 2.0 g / 10 min, and the density was 919 kg / m 3 The melting point was 106° C. Hereinafter, this is referred to as PE1.

[0093] [PE2] Sumikathene L705 (manufactured by Sumitomo Chemical Co., Ltd.), an ethylene homopolymer, was used. The melt flow rate measured at 190°C was 7.0 g / 10 min, and the density was 919 kg / m 3 The melting point was 105°C.

[0094] Ingredients of the [Third layer (outer layer)]

[0095] [PP6] Propylene and ethylene were copolymerized in the gas phase in the presence of a Ziegler-Natta catalyst to obtain a propylene-ethylene random copolymer having a melting point of 158°C and a melt flow rate of 7.0 g / 10 min measured at 230°C. The obtained propylene-ethylene random copolymer is hereinafter referred to as PP6.

[0096] [Example 1] First layer composition: 100% by mass of PP1, 0.05% by mass of calcium stearate, 0.175% by mass of Irganox 1010, 0.075% by mass of Irgafos 3114 (BASF, antioxidant), and 0.14% by mass of Silica 550 (Fuji Silysia Chemical) as an antiblocking agent were mixed in a 20L super mixer (Kawada Manufacturing, SMV-20 type). The mixture obtained was melt-kneaded at 250°C using a single-screw extruder with a diameter of 40 mm (Tanabe Plastics Machine, VS40-28 type, with full-flight screw) to obtain pellets of the first layer composition. The melt flow rate of the obtained pellets measured at 230°C was 6.0g / 10min. Composition for second layer: PP2 50% by mass, PP3 20% by mass, PE1 30% by mass, hydrotalcite 0.01% by mass, Irganox 1010 0.05% by mass, and Irgafos 168 0.05% by mass were mixed in a Henschel mixer to obtain a mixture. The mixture obtained was melt-kneaded at 250°C in a single-screw extruder with a diameter of 65 mm to obtain pellets of the composition for the second layer. The melt flow rate of the obtained pellets measured at 230°C was 2.7g / 10min. Composition for third layer: 100% by mass of PP6, 0.01% by mass of hydrotalcite, 0.15% by mass of Irganox 1010, and 0.15% by mass of Irgafos 168 were mixed in a 20L super mixer (Kawada Manufacturing Co., Ltd., SMV-20 type) to obtain a mixture. The mixture obtained was melt-kneaded at 250°C using a single-screw extruder with a diameter of 40 mm (Tanabe Plastics Machine Co., Ltd., VS40-28 type, with full-flight screw) to obtain pellets of the composition for the third layer. The melt flow rate of the obtained pellets measured at 230°C was 7.0g / 10min.

[0097] Each pellet was introduced into each extruder of a feedblock-type T-die (die width 1250 mm, lip opening 0.8 mm) equipped with three extruders, and melt extrusion was performed at a die temperature of 240°C so that the third layer thickness ratio was 10%, the second layer thickness ratio was 80%, and the first layer thickness ratio was 10%. The extruded molten film was cooled and solidified on a chill roll rotating at 80 m / min at a cooling temperature of 40° C. to obtain a 30 μm thick film consisting of Layer 1, Layer 2, and Layer 3. The polymer components contained in each layer of the film are shown in Table 1.

[0098] A biaxially oriented nylon film having a thickness of 12 μm was laminated by dry lamination on the surface of the obtained film other than the first layer side to obtain a composite film. The obtained composite film was used to measure the peel strength curve between the film and the polypropylene sheet by the above-mentioned peel test method. The peel strength curve showed a maximum value at a peel length of 0 mm to 5 mm, and the maximum value was 11 N / 15 mm, and the test piece was able to be peeled without breaking until the entire seal part was peeled off. The peel strength was 8 N / 15 mm, and the difference between the maximum and minimum values ​​of the peel load within a peel length range of 10 mm to 20 mm was 3 N / 15 mm, and the peel behavior was good without leaving any film residue. Analysis of images taken with a transmission electron microscope confirmed a sea-island type phase separation structure consisting of a continuous phase and a discontinuous phase, and S1 / S2 was 1.50.

[0099] [Example 2] A film and a composite film were obtained and evaluated in the same manner as in Example 1, except that a pellet blend of 50% by mass of PP4, 20% by mass of PP5, and 30% by mass of PE1 was used as the composition for the second layer. The peel strength curve showed a maximum value at a peel length of 0 mm to 5 mm, and the maximum value was 10 N / 15 mm, and the test piece was able to be peeled without breaking until the entire seal part was peeled off. The peel strength was 7 N / 15 mm, and the difference between the maximum and minimum values ​​of the peel load within a peel length range of 10 mm to 20 mm was 1 N / 15 mm, and the peel behavior was good without leaving any film residue. Analysis of images taken with a transmission electron microscope confirmed a sea-island type phase separation structure consisting of a continuous phase and a discontinuous phase, and S1 / S2 was 1.37.

[0100] [Example 3] The evaluation was performed in the same manner as in Example 2, except that the composition for the third layer was not used, and the composition for the second layer was introduced into two of the three extruders, including the central one, and melt-extruded so that the thickness ratio of the first layer was 10% and the thickness ratio of the second layer was 90%, to obtain a film having a thickness of 30 μm with a structure of the first layer / second layer. The peel strength curve showed a maximum value at a peel length of 0 mm to 5 mm, and the maximum value was 9 N / 15 mm, and the test piece was peelable without breaking until all the sealed parts were peeled off. The peel strength was 8 N / 15 mm, and the difference between the maximum and minimum values ​​of the peel load within a peel length range of 10 mm to 20 mm was 2 N / 15 mm, and the peel behavior was good without leaving any film residue. Analysis of images taken with a transmission electron microscope confirmed a sea-island type phase separation structure consisting of a continuous phase and a discontinuous phase, with S1 / S2 being 1.27.

[0101] [Example 4] A film and a composite film were obtained and evaluated in the same manner as in Example 2, except that PE2 was used instead of PE1. The peel strength curve showed a maximum value between 0 mm and 5 mm of peel length, and the maximum value was 8 N / 15 mm, and the test piece was able to be peeled without breaking until all the sealed parts were peeled off. The peel strength was 7 N / 15 mm, and the difference between the maximum and minimum values ​​of the peel load within the peel length range of 10 mm to 20 mm was 2 N / 15 mm, and the peel behavior was good without leaving any film residue. Analysis of images taken with a transmission electron microscope confirmed a sea-island type phase separation structure consisting of a continuous phase and a discontinuous phase, and S1 / S2 was 1.26.

[0102] [Example 5] A film and a composite film were obtained and evaluated in the same manner as in Example 2, except that the extruded molten film was cooled and solidified by a chill roll rotating at 60 m / min. The peel strength curve showed a maximum value at a peel length of 0 mm to 5 mm, and the maximum value was 9 N / 15 mm, and the test piece was able to be peeled without breaking until all the sealed parts were peeled off. The peel strength was 8 N / 15 mm, and the difference between the maximum and minimum values ​​of the peel load within a peel length range of 10 mm to 20 mm was 3 N / 15 mm, and the peel behavior was good without leaving any film residue. Analysis of images taken with a transmission electron microscope confirmed a sea-island type phase separation structure consisting of a continuous phase and a discontinuous phase, and S1 / S2 was 1.38.

[0103] [Comparative Example 1] As the composition for the second layer, 50% by mass of PP2, 20% by mass of PP3, 30% by mass of PE1, 0.01% by mass of hydrotalcite, 0.05% by mass of Irganox 1010, and 0.05% by mass of Irgafos 168 were mixed in a Henschel mixer to obtain a mixture. The obtained mixture was melt-kneaded at 250°C in a single-screw extruder with a diameter of 40 mm to obtain pellets of the composition for the second layer. A feed block type T-die (die width 600 mm, lip opening 0.8 mm) equipped with three extruders was used for melt extrusion, and the extruded molten film was cooled and solidified by a chill roll rotating at 20 m / min. Except for this, a film and a composite film were obtained and evaluated in the same manner as in Example 1. The peel strength curve showed a maximum value between the peel length of 0 mm and 5 mm, and the maximum value was 10 N / 15 mm, and the test piece was peeled without breaking until all the sealed parts were peeled off. The peel strength was 8N / 15mm, and the difference between the maximum and minimum peel loads within the peel length range of 10mm to 20mm was 2N / 15mm, resulting in some residual film. Analysis of images taken with a transmission electron microscope confirmed a sea-island type phase separation structure consisting of a continuous phase and a discontinuous phase, with an S1 / S2 ratio of 1.25.

[0104] [Comparative Example 2] As the composition for the second layer, 70% by mass of PP2, 30% by mass of PE1, 0.01% by mass of hydrotalcite, 0.05% by mass of Irganox 1010, and 0.05% by mass of Irgafos 168 were mixed in a Henschel mixer to obtain a mixture. The obtained mixture was melt-kneaded at 250°C in a single-screw extruder with a diameter of 40 mm to obtain pellets of the composition for the second layer, and a film and a composite film were obtained and evaluated in the same manner as in Comparative Example 1. The peel strength curve showed a maximum value in the peel length range of 0 mm to 5 mm, and the maximum value was 8 N / 15 mm, and the test piece could be peeled up to a peel length of 25 mm without breaking. The peel strength was 4 N / 15 mm, and the difference between the maximum and minimum values ​​of the peel load in the peel length range of 10 mm to 20 mm was 1 N / 15 mm, and a film residue was generated. Analysis of images taken with a transmission electron microscope confirmed that the polymer had an islands-in-a-sea type phase-separated structure consisting of a continuous phase and a discontinuous phase, with an S1 / S2 ratio of 0.85.

[0105] [Comparative Example 3] As the composition for the second layer, 65% by mass of PP2, 35% by mass of PE1, 0.01% by mass of hydrotalcite, 0.05% by mass of Irganox 1010, and 0.05% by mass of Irgafos 168 were mixed in a Henschel mixer to obtain a mixture. The obtained mixture was melt-kneaded at 250°C in a single-screw extruder with a diameter of 40 mm to obtain pellets of the composition for the second layer, and a film and a composite film were obtained and evaluated in the same manner as in Comparative Example 1. The peel strength curve showed a maximum value in the peel length range of 0 mm to 5 mm, and the maximum value was 8 N / 15 mm, and the test piece was peelable without breaking until all the sealed parts were peeled off. The peel strength was 3 N / 15 mm, and the difference between the maximum and minimum values ​​of the peel load in the peel length range of 10 mm to 20 mm was 3 N / 15 mm, and a film residue was generated. Analysis of images taken with a transmission electron microscope confirmed that the polymer had an islands-in-a-sea type phase-separated structure consisting of a continuous phase and a discontinuous phase, with an S1 / S2 ratio of 1.05.

[0106] [Table 1]

[0107] As can be seen from the results in Table 1, the films of Examples 1 to 5 which satisfy all of the constituent requirements of the present invention are able to suppress the occurrence of film residue, as compared with the films of Comparative Examples 1 to 3.

Claims

1. A film comprising a phase-separated structure layer having an islands-in-a-sea type phase-separated structure composed of a continuous phase and a discontinuous phase, comprising at least two kinds of olefin-based polymers, The phase-separated structure layer has a cross section in the TD direction that satisfies the following formula (1): The film comprises, as the at least two kinds of olefin-based polymers, a propylene-based polymer and an ethylene-based polymer. 1.26≦S1 / S2 (1) (In the formula, S1 indicates the average area of ​​the discontinuous phase in a region from one surface to a thickness of 0% to 4% relative to 100% of the thickness of the phase-separated structure layer. S2 indicates the average area of ​​the discontinuous phase in the region from one surface to 48% to 52% of the thickness relative to 100% of the thickness of the phase-separated structure layer.)

2. The film according to claim 1 , which satisfies the following formula (2): 1.26≦S1 / S2≦1.50 (2) (In the formula, S1 and S2 have the same meanings as S1 and S2 above.)

3. the continuous phase is formed from a propylene-based polymer containing 90% by mass or more of structural units derived from propylene, 3. The film according to claim 1, wherein the discontinuous phase is formed from at least one selected from the group consisting of propylene-based polymers and ethylene-based polymers containing less than 90% by mass of structural units derived from propylene.

4. The film according to any one of claims 1 to 3, wherein the at least two kinds of olefin-based polymers include a propylene homopolymer, a propylene random copolymer, and an ethylene polymer.

5. The at least two kinds of olefin-based polymers include a propylene-based multistage polymer produced in two or more stages and composed of at least two kinds of propylene-based polymer components, a propylene-based random copolymer, and an ethylene-based polymer; The film according to any one of claims 1 to 3, wherein the propylene-based multistage polymer comprises a propylene homopolymer component (A) and a propylene copolymer component (B).

6. The film of any one of claims 1 to 5, further comprising a sealing layer.

7. A method for producing the film of any one of claims 1 to 6, comprising the steps of: A step of melt-kneading a composition containing at least two kinds of olefin-based polymers; A step of extruding the melt-kneaded composition onto a cooling roll rotating at a speed of 50 m / min or more; forming the extruded composition into a film; A method for producing a film comprising the steps of:

Citation Information

Patent Citations

  • Easily cleavable film

    JP1987222831A

  • Easily tearable film

    JP1988087221A

  • Surface protection polypropylene based resin film roll and surface protection film roll

    JP2010184990A

  • Easily openable laminated film and lid material using the same

    JP2013136151A

  • Multilayered film

    JP2020001386A